9th Atmospheric Flight Mechanics Conference 1982
DOI: 10.2514/6.1982-1343
|View full text |Cite
|
Sign up to set email alerts
|

Angular motion of a spinning projectile with a viscous liquid payload

Abstract: The flidirgs in this report are not to be construed as an official Departnent of the Army position, unless so designated by other authorized documents.'~a not 0-ti t~t* kda m ven o r Mv CO . Ma -Pre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Previous comparisons between computed pressures by Murphy 9 and Gerber et al 0 for high Reynolds numbers and this measurement system have been consistent. degrees.…”
supporting
confidence: 74%
“…Previous comparisons between computed pressures by Murphy 9 and Gerber et al 0 for high Reynolds numbers and this measurement system have been consistent. degrees.…”
supporting
confidence: 74%
“…Murphy 4 has shown that the average value of the liquid moment is increased by a reduction in Re. Hence, for a nonresonant cylinder, such as c/a -3/2, large Re behavior is stable while low Re behavior could be unstable.…”
Section: E Comparison With Flight Datamentioning
confidence: 99%
“…i First order viscous boundary layer corrections to the Stewartson 1 theory were carried out by Wedemeyer 2 and Murphy. 3 A method for calculating the linear liquid moment using the full linear viscous equations with boundary layer corrections confined only to the endcanps was also presented by Hall and Sedney and Gerber 4,5 . A further interest to the army is to consider a series of uniform circular cylinders stacked end to end separated by impenetrable end-caps (candle-sticks).…”
Section: Introductionmentioning
confidence: 99%